Investigating the role of electronic insurance on decreasing exporting charges risks - Farideh MosallaiZade (Management Science Letters)
Nowadays, the electronic insurance (EI) is one the electronic services, which is used in most countries, and that is one effective factor in developing the exporting products and services. On the other hand, the incurrence industry and very especially EI represent their importance both domestically and internationally. One of the ways for transferring the exporting risks is to transfer the risks to the insurer. This paper examines the characteristics of EI and the effects of decreasing the exporting risk charges. The proposed study designs a questionnaire in the form of Likert scale, the validity of the questionnaire is validated by some the experts' viewpoints and the Cronbach' alpha is measure as 0.794. The results of applying Freedman test have disclosed that facilitating export activities was the most important factor followed by access to target export market information.